08 Are DOACs dead? Or do they still have a role in SLE/APS?. (6th April 2022) - Isenberg, David
Abstract : Since its development in the 1950s, the vitamin K (VKA) antagonist warfarin has been a standard anticoagulant, which for 40 years has utilised the International Normalisation Ratio (INR) to regulate the required dose. Although effective in the treatment of blood clots and reducing the risk of stroke in atrial fibrillation, its use necessitates significant food restrictions and the avoidance of many types of drugs. In contrast, direct oral anticoagulants (DOACs) are fixed-dose, more predictable, require no routine monitoring, have no interactions with food or alcohol and many fewer drug interactions than warfarin. The RAPS study demonstrated that rivaroxaban is not inferior to warfarin in the treatment of patients with venous thromboembolism with a target INR of 2–3. 1 Quality of life consideration favoured rivaroxaban in that study. Notably, 27% of the patients in this trial were triple positive for anti-phospholipid antibodies (APAbs). In contrast, in the TRAPS trial, patients with high risk triple-positive antiphospholipid syndrome (APS) on rivaoxaban were shown to be at increased risk of developing thromboembolic events 2 – a concern mirrored by a report from Ordi-Ross et al, although the numbers of arterial events comparing rivaroxaban and warfarin was not in fact statistically significantly different. 3 In addition, there are several early studies reporting approximately 3% of patients per year develop recurrent thrombosis while on warfarin. 4 Currently, the Medicine and Healthcare Products Regulatory Agencies (MHRA) in the UK advise that DOACs are not recommended for patients with a history of thrombosis who are diagnosed with APS and particularly for those who are triple positive. DOACs may, however, be considered in patients who have difficulty achieving a target INR despite compliance with warfarin. EULAR recommendations indicate that rivaroxaban should not be used in APS patients with triple APAbs positivity. However, there is an ongoing need for a prospective evaluation of DOACs versus VKA inhibitors in patients with provoked venous thromboembolism, particularly in those without triple positive disease. The ongoing RISAPS study (NCT03684564 ) is comparing patients with APS with single/double positivity only for APAbs, who have a history of ischaemic stroke or other brain ischaemic injury. The endpoint is the rate of change in brain white matter hyperintensity volume between baseline and 24 months follow-up assessed on magnetic resonance imaging as a surrogate marker of ischaemic damage. In summary DOACS are not dead…… but their 'existence' in APS/systemic lupus erythematosus is threatened! References: Cohen H, et al . Rivaroxaban versus warfarin to treat patients with thrombotic antiphospholipid syndrome, with or without systemic lupus erythematosus (RAPS): a randomised, controlled, open-label, phase 2/3, non-inferiority trial. Lancet Haematol 2016 Sep;3 (9):e426–36. Pengo V, et a l. Rivaroxaban vs warfarin in high-risk patients with antiphospholipid syndrome. Blood 2018 Sep 27;132 (13):1365–1371. Ordi-Ros J, et al . Rivaroxaban versus vitamin K antagonist in antiphospholipid syndrome: a randomized noninferiority trial. Ann Intern Med 2019 Nov 19;171 (10):685–694. Cohen H, et al . 16th international congress on antiphospholipid antibodies task force report on antiphospholipid syndrome treatment trends. Lupus 2020 Oct;29 (12):1571–1593. Learning Objectives: Explain that while widely used VKAs, notably warfarin, while often effective, have major drawbacks in terms of requirement for regular blood tests, and the avoidance of many types of food and drugs Describe how the RAPS study demonstrated the comparative effectiveness of rivaroxaban compared to warfarin in treatment with venous thromboembolic disease with a target INR of 2–3 Describe how the TRAPS and later studies identified a risk of thromboembolic disease in patients on DOACs compared to warfarin in triple APAb positive patients, although earlier studies demonstrated that there is an increased risk (about 3% per annum) of recurrent thromboembolic risks on warfarin Explain, whilst the current advice from the MHRA and EULAR is to avoid DOACs in the treatment of triple positive APS patients, there remains a desperate need for clinical trials to compare the effectiveness of DOACs with VKAs in single and double positive antiphospholipid antibody APS